The Logic of Logistics Theory, Algorithms, and Applications for Logistics and Supply Chain Management - Simchi-Levi, David; Chen, Xin; Bramel, Julien (Springer Series in Operations Research and Financial Engineering, 2005)
Fierce competition in today's global market provides a powerful motivation for developing ever more sophisticated logistics systems. This book, written for the logistics manager and researcher, presents a survey of the modern theory and application of logistics. The goal of the book is to present the state of the art in the science of logistics management. As a result, the authors have written a timely and authoritative survey of this field that many practitioners and researchers will find makes an invaluable companion to their work.